Práticas educativas em espaços urbanos: possibilidades para a formação de professores da EJA - Saint Clair Marques da Silva (2011)
The present study tried to identify and analyze the potential that educational practices built up in cultural and heritage spaces represented to the formation of teachers who took part in the EJA BH Project, from Belo Horizonte City Hall. The collected data come from Belo Horizonte Municipal Educational Office document resources, from a questionnaire and from narrative interviews done with the participant teachers of EJA BH Project. Our analysis were built through the dialogue among the collected data and the referential originated from the young and adults education field, from the teachers´ formation, from school culture and practices, from patrimony and heritage and from the education to the patrimony, emphasizing the following authors: Chagas, Le Goff, Lowenthal, Fenelon, Bosi, Benjamin, Pollack, Siman e Pereira, Andrade, Faria Filho, Nóvoa, Pimenta, Tardif e Lessard. At the teachers´ narrative, it is clearly demonstrated the interactions, exchanges and sharing formative value provided by the city cultural and heritage practices, both for students and for themselves. The teachers narrated how those practices and interactions provided them the building of another look at their students, as well as new knowledge. They also narrated about the cultural and heritage value to the achievement, by EJA students, to the city cultural assets and, therefore, the exercise of citizenship education. Finally, the study may demonstrate how the reflections done by teachers over the scholastic practices developed by themselves in cultural and heritage city places are fertilized by the heritage and patrimony fields. In this sense, it can be stated that the teachers´ formation field has the city as a knowledge and sensibilities creator.